Segitiga Friksi dalam Organisasi: Model Integratif Ketidakjelasan Peran, Ketergantungan Tugas, dan Perbedaan Tujuan - Ravel Anwar (Business Administration Department - Universitas Katolik Parahyangan, 2025)
Modern organizational dynamics posit conflict as a logical consequence of complex structural interactions rather than a mere behavioral anomaly. This study aims to synthesize recent literature to develop a predictive conceptual model that integrates role ambiguity, task interdependence, and goal differences as simultaneous determinants. This study conducted a Systematic Literature Review (SLR) following the PRISMA 2020 protocol. Data were extracted from Scopus, ScienceDirect, and Google Scholar databases spanning 2020–2025 to capture current dynamics. Through rigorous selection, 45 empirical articles were analyzed using thematic analysis assisted by NVivo 12. The study confirms the formation of a